DOI: 10.11606/d.9.2001.tde-23012015-150441
|View full text |Cite
|
Sign up to set email alerts
|

Determinação simultânea dos ácidos hipúrico e metil hipúrico urinários por cromatografia gasosa visando a biomonitorização de trabalhadores expostos por tolueno e ao xileno

Abstract: Ao DF. Bõfrs-, âã MediC-Prev ae São P'àulO, pela ajuda preciosa que permitiu a c:ofet:.ã-ctas-amostras:----- - o xileno apresenta outro processo de formação que é a transalquilação do tolueno e aromáticos e 9 . O tolueno, sob forma de vapor em alta temperatura e pressão, reage em presença de um catalisador metálico 22. O tolueno e o xileno são empregados no Brasil como solventes em diversos segmentos industriais do mercado, destacando-se principalmente os de tintas, tíneres, vernizes, adesivos e colas, bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
1
0
0
Order By: Relevance
“…Although several studies demonstrate the influence of alcohol and tobacco consumption on HA levels [ 34 , 35 ], since toluene is part of the composition of cigarettes [ 36 ], no significant differences were observed in the urinary excretion of this metabolite in relation to alcohol and tobacco consumption, in the GSW group. This finding agrees with other studies that demonstrated that these factors did not significantly alter baseline levels of the HA biomarker [ 33 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although several studies demonstrate the influence of alcohol and tobacco consumption on HA levels [ 34 , 35 ], since toluene is part of the composition of cigarettes [ 36 ], no significant differences were observed in the urinary excretion of this metabolite in relation to alcohol and tobacco consumption, in the GSW group. This finding agrees with other studies that demonstrated that these factors did not significantly alter baseline levels of the HA biomarker [ 33 , 37 ].…”
Section: Discussionsupporting
confidence: 93%